NGF and BDNF in pediatrics syndromes. (February 2023) - Ferraguti, Giampiero; Terracina, Sergio; Micangeli, Ginevra; Lucarelli, Marco; Tarani, Luigi; Ceccanti, Mauro; Spaziani, Matteo; D'Orazi, Valerio; Petrella, Carla; Fiore, Marco
Abstract: Neurotrophins (NTs) as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) play multiple roles in different settings including neuronal development, function and survival in both the peripheral and the central nervous systems from early stages. This report aims to provide a summary and subsequent review of evidences on the role of NTs in rare and non-common pediatric human diseases associated with changes in neurodevelopment. A variety of diseases has been analyzed and many have been linked to NTs neurobiological effects, including chronic granulomatous disease, hereditary sensory and autonomic neuropathy, Duchenne muscular dystrophy, Bardet-Biedl syndrome, Angelman syndrome, fragile X syndrome, trisomy 16, Williams-Beuren syndrome, Prader-Willi syndrome, WAGR syndrome, fetal alcohol spectrum disorders, Down syndrome and Klinefelter Syndrome. NTs alterations have been associated with numerous pathologic manifestations including cognitive defects, behavioral abnormalities, epilepsy, obesity, tumorigenesis as well as muscle-skeletal, immunity, bowel, pain sensibility and cilia diseases. In this report, we discuss that further studies are needed to clear a possible therapeutic role of NTs in these still often uncurable diseases. Highlights: NGF and BDNF play key roles in pediatric rare diseases' development. NGF and BDNF may be used as a pharmacological target for pediatric rare diseases' treatment. Further studies are necessary to elucidate a possible therapeutic role of NGF and BDNF in pediatric rare diseases.